2003
DOI: 10.1095/biolreprod.102.012609
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles in Different Stages of Mouse Spermatogenic Cells During Spermatogenesis1

Abstract: During spermatogenesis, diploid stem cells differentiate, undergo meiosis and spermiogenesis, and transform into haploid spermatozoa. Various factors have been demonstrated to regulate this marvelous process of differentiation, but the expression of only a few genes specifically involved in spermatogenesis has been studied. In the present study, different types of spermatogenic cells were isolated from Balb/c mice testes of different ages using the velocity sedimentation method, and we determined the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 26 publications
4
67
0
Order By: Relevance
“…We noticed partial overlapping of our data with the ones published by Yu et al (2003), but also some discrepancies were evident: for instance, cyclin D3 was reported to be not expressed in spermatogonia, but present in spermatocytes. One should note that we used oligonucleotide based DNA chips, in which each gene is represented by 16 couples of probes and mismatch probes, whereas in the gene arrays used by Yu et al each target gene is represented by a single longer oligonucleotide, making the possibility of cross-hybridization easier and hindering the statistical evaluation of the generated signals (see also Section 2).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…We noticed partial overlapping of our data with the ones published by Yu et al (2003), but also some discrepancies were evident: for instance, cyclin D3 was reported to be not expressed in spermatogonia, but present in spermatocytes. One should note that we used oligonucleotide based DNA chips, in which each gene is represented by 16 couples of probes and mismatch probes, whereas in the gene arrays used by Yu et al each target gene is represented by a single longer oligonucleotide, making the possibility of cross-hybridization easier and hindering the statistical evaluation of the generated signals (see also Section 2).…”
Section: Resultssupporting
confidence: 58%
“…Even though, recently, an initial microarray screen of spermatogenic cells at different developmental stages has been reported (Yu et al, 2003), only 1176 mouse target genes were represented in these arrays. We noticed partial overlapping of our data with the ones published by Yu et al (2003), but also some discrepancies were evident: for instance, cyclin D3 was reported to be not expressed in spermatogonia, but present in spermatocytes.…”
Section: Resultsmentioning
confidence: 99%
“…While is it known that GDNF is very important in SSC biological activity in the testis, little is known about what regulates its expression in this tissue. GDNF mRNA and protein have been localized in Sertoli cells (Meng et al 2000), spermatogonia, and spermatids in the mouse (Yu et al 2003). Similar results have been reported for rats and humans (Fouchecourt et al 2006).…”
Section: Regulation Of Gdnf Expressionsupporting
confidence: 84%
“…Large-scale techniques to analyze the transcriptome, such as expressed sequence tags (EST) and cDNA microarrays, have emerged over the past decade, and have been applied to gene expression studies of the mouse testis [1][2][3][4][5][6][7][8][9][10][11][12]. The advent of serial analysis of gene expression (SAGE) has made these technologies more efficient and O'Shaughnessy et al have used SAGE to generate gene expression profiles from the somatic cells of fetal and adult mouse testes [13].…”
mentioning
confidence: 99%